Gossypiboma versus Gossip-Boma - Charanjeet Singh; Mamta Gupta (Case Reports in Radiology)
Gossypiboma, or a retained surgical sponge, is a rare condition, and it can occur after any surgical intervention that requires use of internal swabs. A case of an eight-year-old girl is presented, who had right minithoracotomy for ASD closure. She was finally diagnosed to have a retained surgical sponge in the right pleural cavity.